Estudo de caso avaliativo do currículo integrado do curso de refrigeração e climatização do PROEJA do IFCE - Silva, João Eudes Moreira da (2013)
This investigation is inserted in the Educational Evaluation line of research, curricular evaluation axis, which was developed together with the Graduate Program, School of Education, Federal University of Ceará (UFC). The problem to be investigated was the understanding of how the National Program Curriculum to integrate the Basic Education to the Professional Education for Young and Adults (PROEJA), was made effective in the Refrigeration and Acclimatization course at the Education, Science and Technology Institute of Ceará (IFCE), Fortaleza Campus. In general, this work aims to understand how the integrated curriculum is developing in the course of Refrigeration and Acclimatization at PROEJA, IFCE, Fortaleza Campus, where it has been prescribed and is currently in action, and to identify the socio-institutional and techno pedagogical conditions for making them effective. This research´s specific goal was to identify the context and techno-pedagogical elements from the curricular policies that has been nationally proposed to the PROEJA; to analyze the teacher´s training and their adequacy to the development of an integrated interdisciplinary teaching and analyze the Pedagogical Project of the Refrigeration and Acclimatization course at IFCE/Fortaleza. The theoretical references used were Silva (2007), Freire (1987), Frigotto, Ciavatta e Ramos (2005), Kuenzer (2005), Lewwi (1979), and Vianna (2000), among other researchers interested in Professional Education, education for Young and Adults, and curricular evaluation. This is a study case carried out within a methodological approach of qualitative-quantitative nature. The sources used for this research were teachers, managers, pedagogical consultants; current legislation documents related to professional education, basic education, young and adult education, as well as the Pedagogical Project of the Refrigeration and Acclimatization course. As for the data collection technics, it was used documental analysis, open interviews and structured surveys. The results of this investigation made it clear that IFCE/ campus Fortaleza should take over PROEJA in all its dimensions: structural, political and pedagogical, and a specific training for teachers. The data indicates that the PROEJA´s curricular proposal allows the integration of the syllabus of the general education with the specific education, however, it would not render concrete on its operational part; furthermore, there is not a continuous education policy for the IFCE campus Fortaleza´s professionals. The hypothesis of this work proves that the integrated curriculum for the Refrigeration and Acclimatization course, to be made effective in a satisfactory way in terms of the student´s learning process, requires a specific training for the teachers of the Integrated High School for young and adults and create institutional and structured conditions required for the teacher to mediate between the prescribed curriculum and the curriculum currently in action.